Analyzing Creativity in the Light of Social Practice Theory - Città, Giuseppe; Gentile, Manuel; Augello, Agnese; Ottaviano, Simona; Allegra, Mario; Dignum, Frank (Frontiers in Psychology, 2019)
In this work, starting from the social practice theory, we identified two kinds of creativity: a situational creativity that takes place when, starting from a defined situation, a social practice is played; and a creativity of habit that concerns the agents' capacity for generating new practices from habit when the situation is not defined or is unexpected. To test this hypothesis, the Torrance Test of Creative Thinking (Verbal Form A) was analyzed in the light of praxeology, and the results are analyzed in a computational creativity perspective.